RB/SR RECORD OF FLUID-ROCK INTERACTION IN ECLOGITES: THE MARUN-KEU COMPLEX, POLAR URALS, RUSSIA - Glodny J.; Austrheim H.; Molina J.F.; Rusin A.I.; Seward D. (My University, 2003)
Rb/Sr internal mineral isochrons in the eclogite facies Marun-Keu metamorphic complex, Polar Urals, Russia, date periods of fluid-rock interaction and record the metamorphic reaction history. The Marun-Keu complex consists of Late Proterozoic to Early Ordovician, mostly igneous rocks that experienced a subduction-related, non-pervasive eclogite facies metamorphism, followed by a local decompression-related amphibolite facies overprint, during the Uralian orogeny. Field observations show that metamorphic reactions as well as ductile deformation are controlled by local availability of a free fluid phase. Isotopic data reveals that availability of fluids similarly exerts control on isotope distribution. From a relic gabbro which has never been infiltrated by free fluids, a premetamorphic Rb/Sr age of 467 ± 39 Ma was obtained. Rb/Sr isochron ages for 14 samples of eclogite and amphibolite facies assemblages, sampled from within or close to metamorphic fluid veins, range from 352 ± 5 Ma to 360 ± 3 Ma. A Sm/Nd isochron for a metagranite yields an age of 354 ± 4 Ma. Taken together, the ages for both prograde and retrograde metamorphic assemblages overlap within analytical uncertainty and yield an average value of 355.5 ± 1.4 Ma, indicating that the metamorphic evolution and incipient exhumation of the Marun-Keu complex proceeded rapidly. The results demonstrate that assemblages preserve their Rb/Sr isotopic signatures as long as they remain devoid of free fluids, and that only fluid-rock interaction may cause Sr isotope redistribution. In addition, the data suggest local fluid-rock equilibrium, low fluid-rock ratios with overall fluid deficiency, and limited fluid mobility at depth. However, some fluids must have been mobile on the km-scale since they can be traced into the suprasubduction zone mantle wedge. Metasomatic veins in the Rai-Iz ophiolite yield a Rb/Sr mineral isochron age of 373.1 ± 5.4 Ma. They are interpreted as evidence for suprasubduction zone metasomatism in an oceanic setting, prior to subduction of the East European margin and associated formation of eclogites in the Marun-Keu complex.We propose that Rb/Sr mineral-isochron ages provide hygrochronological rather than thermochronological constraints. They define the cooling history only in combination with zircon and apatite fission track data. The straightforward interpretation of Rb/Sr mineral ages as cooling ages is obsolete.